LITERATURE REVIEW OF ANALYSIS COMPENSATION, CONTINUOUS TRAINING, AND WORK MOTIVATION ON EMPLOYEE RETENTION IN THE DIGITAL ECONOMY ERA - Muhammad Rasyid Fadhila (Draf Solusi Indonesia, 2023)
This research is a literature review that will examinethe analysis of compensation, continuous training,and work motivation on employee retention in thedigital economy era. This research focuses onemployees at Superindo supermarkets. The researchpopulation was Superindo supermarket employeeswhere the sampling technique used was purposivesampling. This research will use the SPSS statisticaltool as a data processing medium which will then testthe feasibility of the data, research model and answerthe research hypothesis